Geomorphometric Seabed Classification and Potential Megahabitat Distribution in the Amazon Continental Margin - Lavagnino, Ana Carolina; Bastos, Alex Cardoso; Amado Filho, Gilberto Menezes; de Moraes, Fernando Coreixas; Araujo, Lais Silva; de Moura, Rodrigo Leão (Frontiers in Marine Science, 2020)
The geomorphometry of the northeast portion of the Amazon Shelf, along the Brazilian Equatorial Margin (BEM), off the Amazonas River mouth, was analyzed using the Benthic Terrain Modeler, a spatial analysis technique that defines physical megahabitat classes based on seafloor relief heterogeneities. A compilation of bathymetric data was used to explore a regional level model, and novel high-resolution multibeam data were used to detail specific portions of the region, with emphasis on shelf–slope transitions and shelf-edge reefs. The analyses revealed a complex mosaic of benthic megahabitats that are associated to the shelf’s morphology, distance offshore, and sediment discharge and transport. The massive and continuous terrigenous sediment input is associated to a smooth muddy deposit along the inner and mid shelf (Regular Continental Shelf megahabitat). The portions of the shelf that are less influenced by riverine sediment accumulation are rougher and characterized by either sand (Irregular Sand Continental Shelf megahabitat) or carbonate-dominated bottom (Irregular Reef Continental Shelf megahabitat). The most notable difference in terms of morphometric analysis and megahabitats can be observed along the outer shelf and shelf break. The shelf–slope transition megahabitat is marked by ridges in the shelf break and by a more acute depth gradient that forms a distinct outer shelf edge. Three different alongshore sectors were explored in order to describe the heterogeneous megahabitat mosaic in terms of slope and bottom morphology. The western-most sector (S3) is remarkable due to an indistinct separation between ridges and the outer shelf edge, as well as for presenting reefs with up to 20 m high, between 110- and 210-m water depths. The central sector (S2) presents no shelf break and lacks ridges, a feature that seems associated with the long-term sediment accumulation associated to the Amazon Fan. The southern-most sector (S1) does not present an outer shelf edge, only ridges, and presents a number of channels incised in the shelf, comprising an erosive area with sediment bypass across the shelf, and carbonate sedimentation. The continental slope is a vastly diverse domain that may be further divided into a Featured Slope megahabitat with numerous canyons and ravines and a vast area that lacks such features, including a Shallow Gentle Slope megahabitat (<2,000-m water depth), a Steep Slope megahabitat, and a Deep Gentle Slope megahabitat. Our results confirm the usefulness of geomorphometric analyses to define benthic megahabitats and can be used as a starting point in a much-needed marine spatial planning process for the area.